Abnormal white matter integrity in rapists as indicated by diffusion tensor imaging. Issue 1 (December 2016) - Chen, Chiao-Yun; Raine, Adrian; Chou, Kun-Hsien; Chen, I-Yun; Hung, Daisy; Lin, Ching-Po
Abstract Background Recent research has documented structural brain abnormalities in various criminal offenders. However, there have been few brain imaging studies of sex offenders, and none on white matter integrity. The current study tested the hypothesis that rapists, when compared to matched controls, would show abnormal cortical and subcortical white matter integrity. Results Rapists showed significantly increased fractional anisotropy in the internal capsul e in the thalamus, caudate, and globus pallidus, and also in white matter tracts near the angular gyrus, posterior cingulate, frontal pole, lateral occipital cortex, and genu compared to controls matched for age, gender, and educational status. Reduced fractional anisotropy was observed in rapists in the posterior cingulum and in the inferior fronto-occipital fasciculus. Conclusions To our knowledge, this is the first study indicating white matter abnormalities in rapists. Findings indicate abnormalities in white matter connectivity in brain regions involved in reward/motivation and moral judgment, which may predispose rapists to be both over-responsive to sexual reward stimuli and also to make inappropriate moral decisions.